Barrierefreiheit - Zugänglichkeit - Universelles Design Zur Gestaltung teilhabeförderlicher Umwelten - Schäfers, Markus; Welti, Felix (Verlag Julius Klinkhardt, 2021)
Accessible environments enable people with impairments to participate in social life. But what exactly does accessibility mean? What makes a condition in the environment a barrier? What aspects determine whether environments are conducive or obstructive to social participation? How can these aspects be measured, assessed and classified? What does this mean for the planning and assessment of designed environments? The contributions to the book deal with these questions from different disciplinary perspectives. They show the multi-layeredness and complexity of the topic of accessibility. The book is intended to give substance to the discussion on barriers and accessibility - a field that is still little researched - and to inspire interdisciplinary dialogue and reflection on practice.